Berberine inhibits growth and inflammatory invasive phenotypes of ectopic stromal cells: Imply the possible treatment of adenomyosis - Li Liu; Ning Luo; Jing Guo; Yan Xie; Li Chen; Zhongping Cheng (Elsevier, 2018)
Adenomyosis is a common chronic gynecological disorder with some tumor-like properties, including aberrant proliferation, invasion and migration. Berberine (BBR) is an isoquinoline derivative alkaloid with diverse pharmacological activities for the treatment of a wide variety of diseases. However, the effect of BBR on adenomyosis has not been understood. This study was to evaluate the potential therapeutic effect of BBR on ectopic endometrial stromal cells (EESCs) isolated from patients with adenomyosis. Our data showed that BBR significantly inhibited the proliferation and viability of eutopic endometrial stromal cells (EuESCs) and EESCs, while slightly affected the growth of normal endometrial stromal cells (NESCs). BBR markedly exhibited a growth inhibitory effect on EESCs by triggering apoptosis and cell cycle arrest, and alleviating the expression of inflammatory invasive phenotypes (IL-6, IL-8, TGF-β, EGF, VEGF, and MMP2). The alleviation of inflammatory invasive phenotypes partly involved nuclear translocation of NFκB/p65 and stat3 activation. Taken together, BBR markedly inhibits the growth of EESCs and might be a promising new strategy for the treatment of adenomyosis. Keywords: Berberine, Adenomyosis, Stromal cell, Apoptosis, Inflammatory phenotype